SEMANTIC ANALYSIS OF CORPOREALITY IN THE POETIC DISCOURSE OF MOMČILO NASTASIJEVIĆ (Heritage, 2020)
The paper semantically analyzes the corporeality in the poetic discourse of Momčilo Nastasijević. The verses indicate the semantic structure of the body through its sensuous, affective and ontological segment. The conceptual distinction between the body and corporeality is emphasized, by pointing to the body as a conceptual domain that is conceptualized through the plant world and corporeality as a quality that arises in bodily intercommunication. Corporeality is semantically formed in the fusion of bodily relationship and the dynamics of its meaning finds the words whose semantic content is dynamic, and in most cases these words are lexemes that denote processes in the vegetative world. Corporeality is not limited to the material appearance of the body, but is recognized as a space in which the body exists incorporeal and immaterial. Corporeality arises in the human physical-physiological substance of the body, but at the same time it is in the human being an inseparable form with the soul (feelings). There is an ontological component of meaning of the corporeality based on Christian ethical theses. Corporeality is also a metaphysical presupposition of human existence. It is confirmed in the songs with verses about the insatiability of thirst, i.e., eros, which is not bare libido sexualis, but longing and necessity for another being, i.e., the necessity to know the spiritual and divine principle through another body (another being). The function of desire is also shown in conceptual representations of corporeality. According to the poet’s essays, desire is the disharmonization of the human personality, and that connotation predetermines the negative meaning of corporeality. In that sense, the body is a state of death and carries the potential for perversion. Hence, the thought of bodily renunciation and prohibition of bodily desire appears in the verses, which is also the influence of Christian views on Nastasijević’s poetics and semantics of corporality.
Keywords: notion of corporeality, body, semantic analysis, poetry, desire, physiology, ontology, Momčilo Nastasijevic